The Effect of Principal’s Management and Learning Media on Student’s Achievement - Damayanti, Rahmi; Fitria, Happy; Wahidy, Achmad (Graduate Program Magister Manajemen Pendidikan, 2024)
The purpose of this study was to determine the effect of principal management and learning media on student achievement at SD Negeri Gugus 11 Prabumulih Timur. This study was conducted on elementary school teachers and students in the East Prabumulih cluster. The sample size was taken as many as 89 samples of public elementary school teachers and students. The sampling technique was purposive sampling, namely, where the respondents who were taken were part of the teachers and students. The data were collected by distributing questionnaires using a 5-point Likert scale to measure 69 statement items. The analysis technique used is multiple linear regression analysis. The results showed that: 1) principal’s management and teacher’s learning media simultaneously and significantly influence student’s achievement; 2) principal’s management partially and significantly influences student’s achievement; and 3) teacher’s learning media partially influences and significant to student’s achievement in SD Negeri Gugus 11 Prabumulih Timur. This paper contributes to more give attention the principal’s management and teacher’s learning media to have good student’s achievement.